Fikih Legal Opinion (Reinterpretasi Hukum Gadai dalam Perspektif Hukum Perdata dan Hukum Islam) - Miftahul Ulum (STAI Syaichona Moh. Cholil Bangkalan, 2019)
Pawn is the right to a movable item that is attached to a person for assistance in the form of giving debt to another person. Submission of the movable goods by the person who owes the party giving the debt, is given as collateral. If in the future the debtor is defaulted, does not repay the debt when it is due, the collateral can be auctioned. Pawnshops based on the Civil Code Article 1150 are pocketing official permission to manage, assist, and develop all forms of financial activities by giving injections of funds to people in the form of financing. Auth (main tasks and functions) of pawning is protecting, fostering, and providing protection in the form of loan funds with the intent and purpose so that people are not caught up in various offers and financial assistance by non-formal financial institutions that relatively utilize the community,